Brainstem Disconnection: Two Additional Patients and Expansion of the Phenotype - Poretti, Andrea; Denecke, Jonas; Miller, Douglas C.; Schiffmann, Holger; Buhk, Jan Hendrik; Grange, Dorothy K.; Doherty, Dan; Boltshauser, Eugen (Neuropediatrics, 2015)
Brainstem disconnection (BD) is a rare posterior fossa abnormality defined by the nearly complete absence of a brainstem segment with the rostral and caudal brainstem portions connected only by a thin cord of tissue. The outcome is poor and the majority of children die within the first 2 months of life without achieving developmental milestones. We report on the cases of two children with BD and a prolonged spontaneous survival. Neither patient required intubation or mechanical ventilation and each survived longer than 2 months (one child died at the age of 8 months, the other is alive at the age of 4.5 years). In addition, patient 1 is the only child with BD reported so far who achieved some developmental milestones. Although the long-term neurodevelopmental outcome of BD remains unfavorable, the expansion of the phenotypic spectrum may be important in terms of counseling.
Keywords: brainstem; brainstem disconnection; brainstem malformation; neuroimaging; neonates; outcome